{4,6-Bis[(E)-1-methyl-2-(pyridin-2-yl-methyl-idene-κN)hydrazinyl-κN]pyrimidine-κN}dichloridocopper(II) methanol disolvate monohydrate - MCCABE, THOMAS; SCHMITT, WOLFGANG; MARZEC, BARTOSZ (My University, 2011)
The title compound, [CuCl2(C18H18N8)]?2CH3OH?H2O, contains a pentacoordinated Cu(II) atom bonded to the tridentate 4,6-bis[(E)-1-methyl-2-(pyridin-2-ylmethylidene)hydrazinyl]pyrimidine ligand and two Cl atoms. The geometry around the CuII atom is distorted square-pyramidal. The molecules pack in the crystal structure via O-HCl, O-HN, C-HCl and C-HO hydrogen bonds, C-H and - interactions [centroid-centroid distances of the pyrimidine-pyridine and pyridine-pyridine interactions are 3.750 (3) and 3.850 (3) ?, respectively], forming sheet-like assemblies.
PUBLISHED
Keywords: Chemistry; Crystallography; Nanoscience & Materials